(untitled) (Jagannath University Journal of Life and Earth Sciences, 2025)
Migration and development are intricately linked through complex economic, social, and political processes. The theoretical debate surrounding migration and development has evolved over time, shifting from early perspectives that viewed migration as a consequence of underdevelopment to more contemporary views that recognize migration as a driver of development. This paper explores the major theoretical frameworks that shape the discourse on migration and development, including modernization theory, dependency theory, world-systems theory, the new economics of labor migration (NELM), and transnationalism. By critically analyzing these theories, this paper aims to illuminate the multifaceted relationship between migration and development and provide insights into contemporary policy debates. Jagannath University Journal of Life and Earth Sciences, 10(1) 1-16